The effectiveness of interventions to treat hypothalamic obesity in survivors of childhood brain tumours: a systematic review. (22nd May 2017) - Wang, K‐W.; Chau, R.; Fleming, A.; Banfield, L.; Singh, S. K.; Johnston, D. L.; Zelcer, S. M.; Rassekh, S. R.; Burrow, S.; Valencia, M.; de Souza, R. J.; Thabane, L.; et al.
Summary: Background: Survivors of childhood brain tumours (SCBT) are at risk of type 2 diabetes and cardiovascular diseases. Obesity is a major driver of cardiometabolic diseases in the general population, and interventions that tackle obesity may lower the risk of these chronic diseases. The goal of this systematic review was to summarize current evidence for the presence of interventions to manage obesity, including hypothalamic obesity, in SCBT. Methods: The primary outcome of this review was the body mass index z ‐score change from baseline to the end of the intervention and/or follow‐up. Literature searches were conducted in PsycINFO, CINAHL, the Cochrane Library, Medline, SPORTDiscus, EMBASE and PubMed. Two reviewers completed study evaluations independently. Results: Eleven publications were included in this systematic review (lifestyle intervention n = 2, pharmacotherapy n = 6 and bariatric surgery n = 3). While some studies demonstrated effectiveness of interventions to manage obesity in SCBT and alter markers of obesity and cardiometabolic risk, the evidence base was limited and of low quality, and studies focused on hypothalamic obesity. We conclude that there is urgent need to conduct adequately powered trials of sufficient duration, using existing and novel therapies to manage obesity, reduce the burden of cardiometabolic disorders and improve outcomes in SCBT.